Survival and Filamentation of Salmonella enterica Serovar Enteritidis PT4 and Salmonella enterica Serovar Typhimurium DT104 at Low Water Activity - Mattick, K. L. (American Society for Microbiology, 2000)
In this study we investigated the long-term survival of and morphological changes in Salmonella strains at low water activity (a(w)). Salmonella enterica serovar Enteritidis PT4 and Salmonella enterica serovar Typhimurium DT104 survived at low a(w) for long periods, but minimum humectant concentrations of 8% NaCl (a(w), 0.95), 96% sucrose (a(w), 0.94), and 32% glycerol (a(w), 0.92) were bactericidal under most conditions. Salmonella rpoS mutants were usually more sensitive to bactericidal levels of NaCl, sucrose, and glycerol. At a lethal a(w), incubation at 37°C resulted in more rapid loss of viability than incubation at 21°C. At a(w) values of 0.93 to 0.98, strains of S. enterica serovar Enteritidis and S. enterica serovar Typhimurium formed filaments, some of which were at least 200 μm long. Filamentation was independent of rpoS expression. When the preparations were returned to high-a(w) conditions, the filaments formed septa, and division was complete within approximately 2 to 3 h. The variable survival of Salmonella strains at low a(w) highlights the importance of strain choice when researchers produce modelling data to simulate worst-case scenarios or conduct risk assessments based on laboratory data. The continued increase in Salmonella biomass at low a(w) (without a concomitant increase in microbial count) would not have been detected by traditional microbiological enumeration tests if the tests had been performed immediately after low-a(w) storage. If Salmonella strains form filaments in food products that have low a(w) values (0.92 to 0.98), there are significant implications for public health and for designing methods for microbiological monitoring.